New Advances on Zika Virus Research - Martinez-Sobrido, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Zika virus (ZIKV) is a mosquito-borne member of the Flaviviridae family that historically has been associated with mild febrile illness. However, the recent outbreaks in Brazil in 2015 and its rapid spread throughout South and Central America and the Caribbean, together with its association with severe neurological disorders-including fetal microcephaly and Guillain-Barré syndrome in adults-have changed the historic perspective of ZIKV. Currently, ZIKV is considered an important public health concern that has the potential to affect millions of people worldwide. The significance of ZIKV in human health and the lack of approved vaccines and/or antiviral drugs to combat ZIKV infection have triggered a global effort to develop effective countermeasures to prevent and/or treat ZIKV infection. In this Special Issue of Viruses, we have assembled a collection of 32 research and review articles that cover the more recent advances on ZIKV molecular biology, replication and transmission, virus-host interactions, pathogenesis, epidemiology, vaccine development, antivirals, and viral diagnosis.